Turn-on fluorescent glutathione detection based on lucigenin and MnO2 nanosheets. Issue 16 (4th December 2019) - Halawa, Mohamed Ibrahim; Wu, Fengxia; Zafar, Muhammad Nadeem; Mostafa, Islam M.; Abdussalam, Abubakar; Han, Shuang; Xu, Guobao
Abstract : A GSH sensing platform using lucigenin as a fluorescent probe in the presence of MnO2 nanosheets was reported for the first time. Abstract : In this work, a glutathione (GSH) sensing nano-platform using lucigenin as a fluorescent probe in the presence of MnO2 nanosheets was reported for the first time. Unlike the earlier fluorescent detection systems based on MnO2 nanosheets, which depend on Förster resonance energy transfer (FRET) or the dynamic quenching effect (DQE), the mechanism of the quenching process of MnO2 nanosheets on lucigenin fluorescence was attributed mainly to a static quenching effect (SQE) with a minor contribution of the inner filter effect (IFE). A double exponential fluorescence decay of lucigenin was obtained in various MnO2 nanosheet concentrations as a result of their SQE and IFE. Based on this phenomenon and taking advantage of the redox reaction between GSH and MnO2 nanosheets, we have developed a switch-on sensitive fluorescent method for GSH via the recovery of the MnO2 nanosheet-quenched fluorescence of lucigenin. A good linearity range of 1.0–150.0 μM with a low limit of detection (S/N = 3) of 180.0 nM was achieved, revealing the higher sensitivity for GSH determination in comparison with the previously reported MnO2 nanosheet-based turn-on fluorescent methods. The developed fluorescent nano-platform exhibits excellent selectivity with successful application for GSH detection in human serum plasma, indicating its good practicability for GSH sensing in biological and clinical applications.